PEMBENTUKAN POKDARWIS DAN PELATIHAN BAHASA INGGRIS SEBAGAI UPAYA PENINGKATAN CITRA DESA WISATA TIMUHUN KECAMATAN BANJARANGKAN KLUNGKUNG - I WAYAN SUARDANA; IB. ASTINA IB. ASTINA; MADE KUSUMA NEGARA (Buletin Udayana Mengabdi, 2006)
ABSTRACT Tourism Awareness group becomes alternative to commence the development tourism in Timuhun village. All these activities begin from a plan coming up from tourism observation in ambulatory Timuhun village better and more comprehensive. As effort of improvement of human resource quality done by training of English and awareness counseling of tour. This activity is ambulatory better as according to expected target. Role of stakeholders to share better is as a means to realize Timuhun as rural tourism resort in Klungkung.